Context Analysis of Determinants In Attracting FDI by Emerging Economies Under The Effects of Covid-19 - Anatol MELEGA; Anamaria Geanina MACOVEI; Veronica GROSU; Marius Sorin CIUBOTARIU (Communications of International Proceedings, 2021)
The purpose of this paper is to analyze and identify the determinants of FDI in emerging economies in the previous and peak period of the COVID-19 pandemic and to quantify the contribution of economic and financial information reported by companies operating in emerging economies for attracting new sources of investment. Thus, in order to achieve the established goal, we pursued the following objectives: O1 - analysis of the dynamics of FDI in 1990-2020 period in emerging economies and identification of the determinant factors in attracting them; O2 - analysis of the contribution in attracting investments of the economic and financial information that was reported by companies operating in emerging countries. The research results consist in the development of an evaluation model of the rate of invested capital (ROIC) in relation with PBV, ROE, EV, EVA. The usefulness of the model is especially relevant for current and potential investors interested in emerging markets, but also for other categories of stakeholders.
Keywords: foreign direct investment; emerging economies; ROIC; COVID-19.